Electric bicycles : a guide to design and use - Morchin, William C., 1936-; Oman, Henry, 1918-; IEEE Xplore (Online Service); Wiley-Interscience (Hoboken, New Jersey : Wiley, 2006)
Design or build a battery-powered electric bicycle For much of the world, bicycles are a transportation mainstay. Electric bicycles--powered by a rechargeable battery pack--are proven to deliver the highest possible energy efficiency, even compared to pedal bikes. A transportation alternative to fossil fuels, electric bicycles are fast catching on, in part because they don't require factory assembly. End-users can easily construct them with available components.The text reveals important techniques, data, and examples that allow readers to judge various propulsion setups--used in both home- and factory-made bikes--and estimate speed and travel distance for each. Numerous charts clearly present the costs, benefits, and trade-offs between both commercial and user-converted models.Key features include:. Estimating motor-performance for wind, hill, and cruising power requirements. Estimating battery capacity and a thorough description of battery charging. Motor and motor-control options. Evaluating motor-to-wheel coupling options. Placement of propulsion components. Configurations and performance. How systems-engineering techniques can produce electric-bicycle designs that have long travel range and low life-cycle cost. Testing. Developments to watchA comprehensive resource for harnessing innovation, Electric Bicycles is the definitive practical guide to taking full advantage of this exciting alternative energy technology.
8 Developments to Watch -- 8.1 Bicycle Systems -- 8.2 Energy Sources -- 8.3 Solar Charging Systems -- 8.4 High-Efficiency Motors -- 8.5 Controllers -- Appendix: Table of Conversion Factors for Units of Measure -- Index.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/21/2015.
Keywords: Electric bicycles; Electric bicycles -- Design and construction; Electronic books